The Belt and Road Initiative as Multiple Geographies of Knowledge Production. (26th October 2021) - Yang, Yang
Abstract : The Belt and Road Initiative (BRI) has attracted wide scholarly attention. However, discussions among social scientists on BRI have largely premised on the academic infrastructure in English language contexts. Academic research on BRI in China has often been only briefly mentioned as background information in English language publications. This disjuncture between scholarship on BRI inside and outside China reflects the multiple geographies of BRI. Thinking through BRI in English and Chinese scholarship, this paper considers how existing and future factors such as funding sources, language politics, political framing of the research and institutional surveillance may yield different intellectual spaces for understanding the knowledge production of BRI.